The Mentality of the Main Character in the As-Shadiiq Yusuf Film Series (A Study of Literary Psychology): Mentalitas Tokoh Utama dalam Film Serial As-Shadiiq Yusuf as (Kajian Psikologi Sastra) - Zulilmi, Muhammad; Suryaningsih, Iin; Zuhdi, Sayyed (Universitas Negeri Jakarta, 2025)
This research aims to identify and describe the mentality of the main character in the series film Prophet Yusuf (as). The focus of the study is the character, traits, and temperament of the character based on their age development, as well as the didactic values contained within to refine the audience's mentality so that they remain optimistic in living their lives under the guidance of Allah SWT. The method used is qualitative research with a descriptive-analytical approach. Data were analyzed using content analysis techniques based on psychological interpretation, which systematically and comprehensively reads and explains text through the showingmethod. The research findings indicate that the main character's mentality is divided into four developmental stages. As a child, he was obedient, steadfast, patient, and full of love. During adolescence, the spirit of influence, steadfastness in truth, keeping promises, and compassion for others emerge. In adulthood, the figure possesses a strong personality, does not succumb to evil, is patient in suffering, is knowledgeable, has noble character, is able to control desires, and is firm against the deceptions of Satan. During his reign, he demonstrated a trustworthy spirit in leadership and intelligence in overcoming problems, particularly in facing fourteen years of harvest and famine.